2014
DOI: 10.1108/ss-12-2012-0043
|View full text |Cite
|
Sign up to set email alerts
|

Application of the concept of cost benefits analysis (CBA) to property level flood risk adaptation measures

Abstract: Purpose -There has been a significant increase in flooding in the UK over the past ten years. During this time, Government policy has moved from investment in flood defences towards encouraging property owners to take responsibility for reducing the impact of flooding. One of the ways in which this can be achieved is for homeowners to adapt their properties to flood risk by implementing property level flood risk adaptation (PLFRA) measures. While there has been some attempt to develop an understanding of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The willingness-to-pay process revealed the difficulties posed in quantifying these benefits, especially the intangible benefits. Research has shown that intangible benefits by their subjective nature are difficult to quantify and are said to be more personal to the victims of flood events [8], [6], [17], [20]. It was, therefore, important to carry out this exercise in order to obtain a full understanding of the benefits of the SuDS scheme to the property owners and to propose an appropriate procedure of eliciting the intangible benefits of the scheme.…”
Section: Benefits From Suds Retrofit Installationmentioning
confidence: 99%
“…The willingness-to-pay process revealed the difficulties posed in quantifying these benefits, especially the intangible benefits. Research has shown that intangible benefits by their subjective nature are difficult to quantify and are said to be more personal to the victims of flood events [8], [6], [17], [20]. It was, therefore, important to carry out this exercise in order to obtain a full understanding of the benefits of the SuDS scheme to the property owners and to propose an appropriate procedure of eliciting the intangible benefits of the scheme.…”
Section: Benefits From Suds Retrofit Installationmentioning
confidence: 99%
“…Although there is research on assessing financial losses due to pluvial flood events (Joseph et al 2014, Jenkins et al 2016, Ke et al 2016, all these approaches take into account only the damage to property and buildings in a general context, and not focusing on the infrastructure and service of the Metro system in the cities where these studies have been carried out. The costs related to the loss of human life and injuries due to flood events, since it depicts a significant challenge its accurate quantification, have not been appropriately studied, remains as the source of the most relevant losses at the economic and social level.…”
Section: )mentioning
confidence: 99%
“…House price then reveal individual preferences [23] regarding the acceptance risk [21], assuming that appropriate control for difference in the property and the location [22] are included. There are difference between prices of houses located inside and outside a specific flood risk zone [15].…”
Section: Problem Statementmentioning
confidence: 99%